Simulasi Pemodelan Crane Hook Tipe Baja AISI A514 Alloy Stell Menggunakan Software Autodesk Inventor Professional 2020 - Cahyadi, Muhammad; Nasrun, Mohamad; Gea, Markus (Jurnal Inovasi Ilmu Pengetahuan dan Teknologi (JIPTEK), 2024)
Lifting aircraft or crane is a combination of a lifting mechanism separately with a frame to lift and or simultaneously move loads that can be hung freely or tied to a crane. Part of the crane hoist has a main component called a crane hook that functions as a load or material hook. The hook is one of the hoisting elements that is very important in crane operations[9]. The types of hooks differ in terms of function, material, form and safety factor, so they must be analyzed, inspected and tested properly so as not to endanger workers in the field. The analysis was carried out numerically using Autodesk Inventor Professional 2020 software[2] . Analysis of hooks generally uses analytical methods or calculations with mathematical models and standardized (common) Algebraic formulas, along with the development of technology today, many engineering sciences have been developed in the field of finite element science which unites mathematics, engineering and science. computer to produce software such as Autodesk Autocad, Autodesk Inventor. In the simulation results of the finite element software on the hook for a loading of 25 tons, the single hook type obtained a maximum stress of 807.809 MPa and the deflection that occurred was 1.444 mm, in the double hook type the maximum stress was 532.632 MPa and the deflection was 0.1871 mm. The simulation results will then be compared with the results of analytical calculations. Analytical calculations for single hooks obtained working stress of 761,729MPa, on double hooks of 387,102 Based on the simulation results and analytical calculations, it can be concluded that the crane hook structure is still within safe limits. This is because the yield strength of the material used in AISI A514 alloy steel is 890 MPa. However, of the three types of hooks at a loading of 25 tons, single hooks have the greatest potential for failure.